PHYSICS LEARNING IN SENIOR HIGH SCHOOL: A STUDY OF DIFFICULTY LEVELS AND TYPES OF LEARNING MEDIA AND NEW MEDIA OPPORTUNITIES - Seira, Erazando Alfa; Fathurohman, Apit; Susiloningsih, Esti (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research is a preliminary study of the need for the development of Augmented Reality- based Physics learning media on the material of Effort and Energy. The purpose of this study is to determine the initial description of the needs of Augmented Reality-based learning media on the material of Effort and Energy of High School Physics. The method in this research is descriptive quantitative. Based on the survey that has been done obtained the results that the material of effort and energy is quite difficult material with a percentage of 61, 75%, so that the development of media on the material of effort and energy is necessary, 100% of teachers agree if developed this learning media and 98% of students are interested and want to use Augmented Reality-based learning media in the learning process so that the development of this media needs to be developed.